The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1194/jlr.m800496-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine 1-phosphate regulates regeneration and fibrosis after liver injury via sphingosine 1-phosphate receptor 2

Abstract: Sphingosine 1-phosphate (S1P), a bioactive lipid mediator, stimulates proliferation and contractility in hepatic stellate cells, the principal matrix-producing cells in the liver, and inhibits proliferation via S1P receptor 2 (S1P 2 ) in hepatocytes in rats in vitro. A potential role of S1P and S1P 2 in liver regeneration and fibrosis was examined in S1P 2 -deficient mice. Nuclear 5-bromo-2′-deoxy-uridine labeling, proliferating cell nuclear antigen (PCNA) staining in hepatocytes, and the ratio of liver weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 43 publications
7
79
2
Order By: Relevance
“…Furthermore, we found that hiPSC-MSCs-Exo could promote hepatocytes proliferation. Consistently, another report also showed that exosomes isolated from mesenchymal stem cells increased hepatocytes proliferation after liver injury induced by carbon tetrachloride [37]. Thus, both results suggest that hiPSC-MSCs derived exosomes are able to trigger homeostatic liver protection after injury.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, we found that hiPSC-MSCs-Exo could promote hepatocytes proliferation. Consistently, another report also showed that exosomes isolated from mesenchymal stem cells increased hepatocytes proliferation after liver injury induced by carbon tetrachloride [37]. Thus, both results suggest that hiPSC-MSCs derived exosomes are able to trigger homeostatic liver protection after injury.…”
Section: Discussionsupporting
confidence: 74%
“…of receptor signaling by extravasated S1P on parenchymal and immune cells in tissues under acute and chronic inflammatory conditions is not well understood but could potentially lead to reparative processes. Whether dysregulated S1P signaling in tissues leads to fibrotic responses is not yet known; however, S1P 2 and S1P 3 have been associated with tissue fibrotic processes in organs, such as the liver, lung, and kidney (81)(82)(83).…”
Section: Mapping In Vivo S1p Signaling Sitesmentioning
confidence: 99%
“…S1P 2 also promotes pathologic angiogenesis and retards normal vascularization in the retinas of mice during hypoxia-induced retinopathy [on the basis of loss-of-function in receptor-null animals ] and, in conjunction with S1P 3 , can provide protection in myocardial ischemia-reperfusion models (Means et al, 2007). It has similarly been linked to reduced fertility, in conjunction with S1P 3 loss , as well as to hepatic wound healing, fibrosis, and regenerative capacity (Serriere-Lanneau et al, 2007;Ikeda et al, 2009).…”
Section: B Sphingosine 1-phosphate Receptorsmentioning
confidence: 99%